Analysis Of The Effect Of Financial Performance On Company Value With Corporate Social Responsibility And Good Corporate Governance Moderation - Eko Edy Susanto; Anita De Grave; Bambang Prihananto (LPPM of NAROTAMA UNIVERSITY, 2021)
This study aims to determine the effect of financial performance on firm value by disclosing corporate social responsibility and good corporate governance as a moderating variable. This research was carried out on the Indonesia Stock Exchange and accessed financial statements at the address www.idx.com. The independent variable in this study is financial performance. Variable moderation is corporate social responsibility and good corporate governance. The dependent variable is the value of the company. This research is a quantitative approach. The data used is secondary data in the form of the company's annual financial statements. The sample in this study is a Mining Company in Indonesia which is listed on the Indonesia Stock Exchange. The data retrieval technique used is the Proposal sampling technique with 17 sample companies within a period of 2 years, namely 2019 to 2020. Data analysis using multiple regression analysis with the help of SPSS version 24 program. The results of the study show (1) financial performance has an influence on company value positively, (2) corporate social responsibility has not been able to moderate financial performance against firm value, (3) good corporate governance has not been able to moderate financial performance against firm value.